Evaluation of foam conditioning effect on groundwater inflow at tunnel cutting face. (29th November 2018) - Liu, Xiao‐Xue; Shen, Shui‐Long; Zhou, Annan; Xu, Ye‐Shuang
Summary: This paper presents an analytical evaluation on the influence of foam conditioning on groundwater inflow at shield tunnel cutting face by the force‐equilibrium principle. Three key variables are highlighted, namely, the maximum foam infiltration distance, the critical infiltration distance, and the hydraulic conductivity of foam‐conditioned soil or rock fissure. To capture the variation of water level induced by foam injection, a dynamic water‐level equation is considered in the force‐equilibrium principle. The proposed analytical equations are employed to analyze a water inflow case during shield tunneling in a weathered mylonite fault. The results indicate that the hydraulic conductivity of foam‐conditioned mylonite and the infiltration distance decrease with an increase of shear stress of foam fluid. A three‐dimensional finite element model is employed to validate the analytical solutions. The comparison between the observed and calculated results confirms that the proposed method can predict groundwater inflow in foam‐conditioned soils.